Islamic Religious Education Learning Strategy for Alpha Generation: A Case Study at Darul Qur'an School Elementary School Semarang City - Ahmad Khanif (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2023)
This study aims to analyse learning strategies and their application for the Alpha generation in Islamic Religious Education (PAI). This study uses qualitative research with observation, interview and documentation as research methods to obtain data. Era 4.0 has increased the need for innovative learning strategies for teachers to facilitate creative and critical thinking among students. Cooperative learning strategy was identified as one of the effective approaches to improve students' problem-solving skills in group discussion on Islamic Education Science. The findings of this study emphasise the importance of identifying appropriate learning strategies for teaching Islamic religious education to the Alpha generation. Teachers need to develop implementation strategies for Islamic religious education in primary schools in order to improve the quality of Islamic religious education and address changes in cognitive, affective and psychomotor domains. In this study, it was found that cooperative learning is an effective teaching strategy for Islamic religious education for the alpha generation. It allows students to engage in problem solving, decision making and learning with their peers. The outcome of the learning process was valued by the class and the learning outcomes were impressive. Based on the findings, it is recommended that teachers use cooperative learning strategies when teaching Islamic Religious Education to the Alpha generation.